The Influence of Motivation, Training, and Self-Efficacy on Employee Performance through Employee Engagement: Library Research - Dewi Untari; Dewi Endah Fajariana; Evi Selvi; Agnia Nurul Huda; Supardi Supardi (Annals of Human Resource Management Research, 2026)
Purpose: This study aims to analyze the influence of Motivation, Training, and Self-Efficacy on Employee Performance through Employee Engagement in the entrepreneurial sector in Indonesia. Using a literature review approach, this study synthesizes the findings from various relevant, internationally indexed academic articles. Research Methodology: This study used a descriptive qualitative research method with a literature review approach. Data were collected from reputable, internationally indexed articles obtained from Scopus, Web of Science, Emerald, Springer, and Google Scholar databases. The selected literature was analyzed using reduction techniques, data presentation in matrix form, and comparative synthesis to identify patterns, similarities, and differences between studies. Results: The results of the study indicate that motivation, training, and self-efficacy have a positive and significant effect on employee performance, both directly and indirectly through employee engagement. Limitations: The limitations of this study lie in its literature review-based nature; therefore, generalization of the results still requires support from empirical research with primary data. Conclusions: This study synthesizes existing scholarly evidence on the relationships among motivation, training, self-efficacy, employee engagement, and employee performance within Indonesia’s entrepreneurial sector. Several theoretically and practically significant conclusions can be drawn from a systematic literature review of internationally indexed academic sources. Contributions: This study contributes by providing an integrative conceptual framework regarding the role of motivation, training, and self-efficacy on employee performance with employee commitment as a mediator.